Sphingolipids and acid ceramidase as therapeutic targets in cancer therapy. (June 2019) - Govindarajah, N.; Clifford, R.; Bowden, D.; Sutton, P.A.; Parsons, J.L.; Vimalachandran, D.
Graphical abstract: Abstract: Background: Sphingolipids have been shown to play a key part in cancer cell growth and death and have increasingly become the subject of novel anti-cancer therapies. Acid ceramidase, a sphingolipid enzyme, has an important role in the regulation of apoptosis. In this review we aim to assess the current evidence supporting the role of sphingolipids in cancer and the potential role that acid ceramidase may play in cancer treatment. Methods: A literature search was performed for published full text articles using the PubMed, Cochrane and Scopus databases using the search criteria string "acid ceramidase", "sphingolipid", "cancer". Additional papers were detected by scanning the references of relevant papers. A summary of the evidence for each cancer subgroup was then formed. Given the nature of the data extracted, no meta-analysis was performed. Results: Over expression of acid ceramidase has been demonstrated in a number of human cancers. In vitro data demonstrate that manipulation of acid ceramidase may present a useful therapeutic target. In the clinical setting, a number of drugs have been investigated with the ability to target acid ceramidase, with the most promising of those being small molecular inhibitors, such as LCL521. Conclusion: The role of the sphingolipid pathway in cancer is becoming very clearly established by promoting ceramide accumulation in response to cancer or cellular stress. Acid ceramidase is over expressed in a variety of cancers and has a role as a potential target for inhibition by novel specific inhibitors or off-target effects of traditional anti-cancer agents. Further work is required to develop acid ceramidase inhibitors safe for progression to clinical trials.